DEVELOPING STUDENTSâ€™ VOCABULARY MASTERY THROUGH STICKY FLANNEL BOOK FOR ELEMENTARY SCHOOL STUDENTS - Rani Setyaning Rum Aisyah; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2017)
The objective of this research is to develop the sticky flannel book for increasing studentsâ€™ vocabulary mastery. The type of this research is Research and Development (R&D). The subjects were 28 learners of the fourth grade in the Minomartani 6 elementary school. The research instruments were questionnaires, interview guidelines, and observation guidelines. The products of this research are sticky flannel book as the medium and â€œEnglish Timeâ€ as the student book based on the genre based approach. There are two units in the book. The title of the first unit is â€œFruitsâ€ and the title of second unit is â€œThings in the Classroomâ€. There are four activities revealing four language skills. The activities apply the four steps of genre based approach: BKOF, MDOT, JCOT, and ICOT.Â The results of expert judgment questionnaires show that the products are categorized into good media and materials, and appropriate to be used in teaching English for the fourth grade of elementary students although there were some revisions that should be done.